(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the fundamental techniques for combining words into sentences effectively. It highlights the importance of basic sentence structures, the use of conjunctions, and different sentence types (simple, compound, complex, and compound-complex). The role of punctuation, modifiers, and parallelism is discussed as essential tools for creating clarity and rhythm in writing. Additionally, the article emphasizes the power of repetition, patterns, and sentence variation to enhance engagement and impact. The conclusions underline the practical application of these principles, offering readers actionable insights to improve their communication skills through thoughtful sentence construction.